2008
DOI: 10.1124/dmd.107.018499
|View full text |Cite
|
Sign up to set email alerts
|

Time-Dependent Effects of Klebsiella Pneumoniae Endotoxin (KPLPS) on the Pharmacokinetics of Theophylline in Rats: Return of the Parameters in 96-Hour KPLPS Rats to the Control Levels

Abstract: ABSTRACT:It has been reported that theophylline is primarily metabolized via hepatic CYP1A1/2, 2B1/2, and 3A1/2, and 1,3-dimethyluric acid (1,3-DMU) is primarily formed via CYP1A1/2 in rats. Compared with control rats, the expression of CYP1A subfamily, 2B1/2, and 3A subfamily significantly decreased 24 h (24-h KPLPS rats) after intravenous administration of lipopolysaccharide derived from Klebsiella pneumoniae (KPLPS) to rats but returned to that in control rats after 96 h (96-h KPLPS rats). After intravenous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…[4,186,189] The metabolism of drugs that were mainly metabolized via the kidney was also dependent on drugs in DMIA or DMIS rats; the metabolism of DA-1131 and rR-RAGE was not altered, but rhIGF-1 increased compared with controls. [57,95,196] The values for CL R of intravenous cefazolin, cefradine, atenolol, and DA-7867 were faster and the values for the AUC of subcutaneous cefotaxime, and oral sodium tungstate and DA-7867 were smaller in DMIA and DMIS rats. [46,54,201,205,210,212] The biliary CL values of intravenous cefoperazone, ouabain, taurocholate, and PAEB were faster and the value for the AUC of oral zopolrestat was smaller in DMIA and DMIS rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4,186,189] The metabolism of drugs that were mainly metabolized via the kidney was also dependent on drugs in DMIA or DMIS rats; the metabolism of DA-1131 and rR-RAGE was not altered, but rhIGF-1 increased compared with controls. [57,95,196] The values for CL R of intravenous cefazolin, cefradine, atenolol, and DA-7867 were faster and the values for the AUC of subcutaneous cefotaxime, and oral sodium tungstate and DA-7867 were smaller in DMIA and DMIS rats. [46,54,201,205,210,212] The biliary CL values of intravenous cefoperazone, ouabain, taurocholate, and PAEB were faster and the value for the AUC of oral zopolrestat was smaller in DMIA and DMIS rats.…”
Section: Discussionmentioning
confidence: 99%
“…[93] In male Sprague-Dawley rats, the formation of 1,3-DMU was primarily mediated via hepatic CYP1A1 and 1A2 and less via CYP3A1 and 3A2 (not via CYP2B1/2, 2C11, 2D1, and CYP2E1). [94,95] The protein expression and mRNA levels of hepatic CYP1A1, 1A2, 3A1, and 3A2 increased in male DMIA and DMIS rats (Table 1), which should have increased the formation of 1,3-DMU. [13,[16][17][18][19]21,22] In fact, after the intravenous administration of 5 mg/kg theophylline to male Sprague-Dawley DMIA rats on the fourth day and DMIS rats on the seventh day, their AUC 1,3-DMU / AUC theophylline ratios became greater (by 184 and 111%, respectively) than those of the controls.…”
mentioning
confidence: 99%
“…The timedependent changes in the hepatic CYP isozymes based on the various enzyme activity tests in ECLPS rats (Gorodischer et al, 1976;Monshouwer et al, 1996;Sewer et al, 1996;Roe et al, 1998;Sewer and Morgan, 1998) are listed in Table II. The changes in the hepatic CYP isozymes in PALPS rats (Ueyama et al, 2005) and in KPLPS rats (Nadai et al, 1998;Ueyama et al, 2005;Yang et al, 2008) have also been reported.…”
Section: Introductionmentioning
confidence: 79%
“…The changes in the hepatic CYP isozymes have been reported in rat models of KPLPS, ECLPS, and PALPS (Nadai et al, 1998;Ueyama et al, 2005;Yang et al, 2008). The pharmacokinetic changes of drugs in KPLPS rats have been reviewed (Yang and Lee, 2007) and the data on PALPS rats are scarce.…”
Section: Introductionmentioning
confidence: 97%
“…Theophylline (5 mg/kg [19] ) CYP1A1/2, 2B1/2 and 3A1/2 [24,27] Significantly faster CLNR (by 49.3%) [19] 6…”
Section: Drugs That Are Altered Pharmacokinetically In Nagase Analbummentioning
confidence: 99%